Eruption time of permanent teeth in Iraqi school children - Nidhal H Ghaib
Mean times of eruption of permanent teeth (except the third molars) were studied crosssectionally in (3000) Iraqi school children aged (6-15) yr. There were no statistically significant differences between the mean ages of corresponding right and left permanent teeth in both sexes. The sequence of eruption was similar in both sexes and in each jaw but in females teeth erupted average of 3 months earlier than in males. The comparison between pervious study and the present study shows that there is a delay in the mean times of eruption of permanent teeth.